Kegiatan Trauma Healing dan Psikososial Pascabencana Gempabumi di Cianjur - Putra, Amal Ramadhani; Rahmat, Hayatul Khairul (Journal of Current Research in Humanities, Social Sciences, and Business, 2025)
This study explores the implementation of trauma healing and psychosocial interventions for children affected by the 2022 Cianjur earthquake. Natural disasters can significantly impact the mental well-being of survivors, especially children, who often experience symptoms such as anxiety, fear, and social withdrawal. Using a literature review method, the research emphasizes play therapy as a core strategy for trauma recovery. Play therapy and creative activities, including educational games and singing, were employed to help children express their emotions, rebuild confidence, and restore social functions. The findings suggest that trauma healing programs that incorporate play-based interventions are effective in addressing both short-term psychological distress and fostering long-term resilience. These activities also promote emotional recovery and social reintegration, contributing to the children's ability to face future challenges.